Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/anie.200902738
|View full text |Cite
|
Sign up to set email alerts
|

Annulation of Metallabenzenes: From Osmabenzene to Osmabenzothiazole to Osmabenzoxazole

Abstract: National Science Foundation of China [20801046, 20872123, J0630429, 20705029

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 57 publications
(15 reference statements)
0
46
0
Order By: Relevance
“…On the other hand, the good stability of our osmacycles in air, water, and heat may enable their potential applications as materials. We have investigated, for the first time, the optical, 25 electrochemical, 15,30 and magnetic 36 properties of these intriguing metalla-aromatics. Some of these properties are promising for use in materials science.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the good stability of our osmacycles in air, water, and heat may enable their potential applications as materials. We have investigated, for the first time, the optical, 25 electrochemical, 15,30 and magnetic 36 properties of these intriguing metalla-aromatics. Some of these properties are promising for use in materials science.…”
Section: Discussionmentioning
confidence: 99%
“…We reported the first S N Ar reaction of metallabenzene under ambient conditions. 25 Osmabenzene 5 reacted with MeONa/MeOH to generate osmabenzothiazole 16 (Scheme 6). The proposed mechanism revealed that the addition reaction of 5 with MeONa gave intermediate C, which then underwent intramolecular nucleophilic attack to afford intermediate D.…”
Section: Osmabenzenementioning
confidence: 99%
See 2 more Smart Citations
“…123 Starting from an osmabenzene, the first osmabenzothiazole and osmabenzoxazole have been synthesised. 124 …”
Section: Introductionmentioning
confidence: 99%